Legal Certainty on Fiduciary Guarantee Deed Based on Power of Attention Under The Leasing Agreement - Recky Rizkiryanto Permana (International Journal of Latin Notary, 2021)
The Fiduciary Guarantee Law requires legal certainty over the implementation of fiduciary guarantee object activities so that special rights can arise from the issuance of a fiduciary guarantee certificate. guarantee binding agreement between creditor and debtor. The power of attorney under the hand used in imposing fiduciary guarantees on credit objects does not contain the actual will of the debtor, this can lead to unilateral arbitrariness by creditors to take credit objects against the will of the debtor so as to eliminate the debtor's rights as the party who controls the object of the fiduciary guarantee. The method used is descriptive-analysis with a normative juridical approach. The research phase uses library research with secondary data and field studies with primary data. This data collection was obtained by means of library research and also interviews obtained by means of field studies. Furthermore, the data were analyzed using the juridical-qualitative method. The use of a power of attorney under the hand as the basis for loading/making a fiduciary deed is "illegitimate". Legal certainty on the Fiduciary Deed based on a Power of Attorney under the hand in a leasing agreement, is not achieved by using a power of attorney as the basis for loading/making a fiduciary deed, then based on the teaching of causality the validity of the fiduciary deed will depend on the validity of the power of attorney that.